In Situ Synthesis of Fluorescent Mesoporous Silica–Carbon Dot Nanohybrids Featuring Folate Receptor-Overexpressing Cancer Cell Targeting and Drug Delivery - Zhao, Shuai; Sun, Shan; Jiang, Kai; Wang, Yuhui; Liu, Yu; Wu, Song; Li, Zhongjun; Shu, Qinghai; Lin, Hengwei (Nano-Micro Letters, 2019)
Multifunctional nanocarrier-based theranostics is supposed to overcome some key problems in cancer treatment. In this work, a novel method for the preparation of a fluorescent mesoporous silica–carbon dot nanohybrid was developed. Carbon dots (CDs), from folic acid as the raw material, were prepared in situ and anchored on the surface of amino-modified mesoporous silica nanoparticles (MSNs–NH2) via a microwave-assisted solvothermal reaction. The as-prepared nanohybrid (designated MSNs–CDs) not only exhibited strong and stable yellow emission but also preserved the unique features of MSNs (e.g., mesoporous structure, large specific surface area, and good biocompatibility), demonstrating a potential capability for fluorescence imaging-guided drug delivery. More interestingly, the MSNs–CDs nanohybrid was able to selectively target folate receptor-overexpressing cancer cells (e.g., HeLa), indicating that folic acid still retained its function even after undergoing the solvothermal reaction. Benefited by these excellent properties, the fluorescent MSNs–CDs nanohybrid can be employed as a fluorescence-guided nanocarrier for the targeted delivery of anticancer drugs (e.g., doxorubicin), thereby enhancing chemotherapeutic efficacy and reducing side effects. Our studies may provide a facile strategy for the fabrication of multifunctional MSN-based theranostic platforms, which is beneficial in the diagnosis and therapy of cancers in future. Highlights: 1 A one-pot method was developed for the preparation of fluorescent mesoporous silica nanoparticles–carbon dots (MSNs–CDs) nanohybrid. 2 The MSNs–CDs nanohybrid showed stable and bright yellow emission, excellent biocompatibility, and specific targeting capability toward folate receptor-overexpressing cancer cells and can be applied as fluorescence imaging-guided drug carriers for effectively delivering anticancer drugs to tumor sites.